The chain mediation effects of general self-efficacy and psychological resilience between physical activity and academic stress among Chinese adolescents - Leng, Haokai; Xiang, Xianlin; Li, Shihong (Frontiers in psychology, 2025)
Excessive academic stress is a significant factor influencing the mental health of Chinese adolescents. This study aimed to examine the relationship between physical activity and academic stress and explore the chain-mediated role of general self-efficacy and psychological resilience. A survey was administered to 1,230 adolescents using the Physical Activity Questionnaire (PAQ-A), the Academic Stress Scale, the General Self-Efficacy Scale (GSES), and the Psychological Resilience Scale. (1) Adolescents' physical activity was negatively correlated with academic stress and positively correlated with general self-efficacy and psychological resilience; general self-efficacy was positively correlated with psychological resilience and negatively correlated with academic stress, while psychological resilience was negatively correlated with academic stress. (2) Physical activity directly affected adolescents' academic stress (β = 0.513, accounting for 64.52% of the total effect) and also indirectly influenced it through three pathways: Physical activity → general self-efficacy → academic stress (β = 0.058, 11.31% of total effect), Physical activity → psychological resilience → academic stress (β = 0.027, 5.26% of total effect), and Physical activity → general self-efficacy → psychological resilience → academic stress (β = 0.098, 19.10% of total effect). Physical activity can directly influence adolescents' academic stress and indirectly affect it through the separate and chain mediation of general self-efficacy and psychological resilience.